Leather Shoes: Repesentation of The Main Character Alif in the Film Ranah 3 Warna (Cinematology: Journal Anthology of Film and Television Studies, 2024)
Ranah 3 Warna is a film based on a novel entitled "Ranah 3 Warna". As a continuation of the film Negeri 5 Menara, the film Ranah 3 Warna was released 9 years after the previous film and tells the story of the steps to reach the tower from the character Alif. The role of leather shoes in the film is a representation of Alif's character. This representation is shown from the beginning of the film to the end of the film. There are quite a few images in films that focus on shoes, where shoes are just an object. Representation is something that represents a situation. Alif's character is described as a strong person, even though he is hurt, he still accompanies him, and is able to adapt to a new environment that suits him. This research uses Charles Sander Pierce's semiotic theory to better understand signs, objects and interpretants. This research aims to determine the representation of leather shoes in the film Ranah 3 Warna on the main character. The method used in this research uses analytical descriptive data collection techniques using the Semiotics approach from Charles Sander Pierce. This research will dissect the representation of leather shoes which is often the focus in films with the character Alif as the main character. From this research, the data obtained shows that Alif's decision making on leather shoes is a representation of the main character, where Alif continues to be strong with himself, just like genuine leather shoes.